Iron-Deficiency Anemia and Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence of iron-deficiency anemia (IDA) in young children at the time of stroke and in age-matched healthy controls was compared in a case-control study conducted at the Hospital for Sick Children, Toronto, Canada.